Electric pole residual slurry composite admixture as well as preparation method and application thereof

By homogenizing the pole residual slurry and combining it with other components, the pole residual slurry composite admixture is prepared, which solves the problem of residual slurry treatment in traditional pole production, and realizes the recycling of resources and the improvement of concrete performance.

CN119528482APending Publication Date: 2025-02-28YUNNAN JINGYI ELECTRIC POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714394.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

Smart Images

  • Figure BDA0005156571330000111
    Figure BDA0005156571330000111
  • Figure BDA0005156571330000112
    Figure BDA0005156571330000112
  • Figure BDA0005156571330000121
    Figure BDA0005156571330000121
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses an electric pole residual slurry composite admixture and a preparation method and application thereof.The preparation method of the electric pole residual slurry composite admixture comprises the following steps that 1, density detection is conducted on collected electric pole residual slurry, and the density of the collected electric pole residual slurry is detected; adding a corresponding amount of saturated calcium hydroxide solution according to the density to carry out residual slurry homogenization treatment; adding a sodium gluconate solution and a defoaming agent, and uniformly mixing to obtain a residual slurry component; (2) mixing silica fume, fly ash and water, adding super absorbent resin and sodium hexametaphosphate, and stirring uniformly to obtain a suspension component; and (3) uniformly mixing the mixed residual slurry component and the suspension component to obtain the electric pole residual slurry composite admixture. Through a specific treatment process and a mix proportion design method, cyclic utilization of the residual slurry of the electric pole is realized, the workability, strength and durability of the concrete are greatly improved, and meanwhile, the production cost and environmental pollution are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an electric pole residual slurry admixture and a preparation method and application thereof. Background Art

[0002] As the country and society pay more and more attention to environmental protection and sustainable development, the environmental pollution and resource waste caused by the traditional production methods in the building materials industry have become increasingly prominent. At the same time, with the aging of the population structure and the continuous increase in labor costs, energy conservation, emission reduction and improving labor efficiency have become important issues facing enterprises. In the production process of electric poles, traditional methods often produce a large amount of residual slurry. If these residual slurries are not properly handled, they will not only cause waste of resources, but also may cause pollution to the environment. In addition, traditional production methods also have problems such as low production efficiency and high material costs. Therefore, it is of great significance to develop a high-performance admixture that can recycle the residual slurry of electric poles and improve the performance of concrete. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a composite admixture of electric pole residual slurry and a preparation method and application thereof, aiming to achieve the recycling of electric pole residual slurry and reduce production costs.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing a composite admixture of residual slurry of electric poles, comprising the following steps:

[0006] (1) Residual slurry homogenization treatment: The collected pole residual slurry is subjected to density detection, and the amount of saturated calcium hydroxide solution to be added is calculated according to the density. The calculated saturated calcium hydroxide solution is added to the pole residual slurry and stirred thoroughly;

[0007] (2) adding sodium gluconate solution and defoamer, and mixing evenly to obtain a residual slurry component;

[0008] (3) mixing silica fume, fly ash and water, adding super absorbent resin and sodium hexametaphosphate and stirring, and mixing evenly to obtain a suspension component;

[0009] (4) The residual slurry component and the suspension component are mixed and stirred evenly to obtain the electric pole residual slurry composite admixture.

[0010] Furthermore, in the step (1), the time for detecting the density of the residual slurry of the electric pole is within 5 minutes after the residual slurry of the electric pole is poured out; the amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M; where M is the weight of the residual slurry to be treated, and ρ0 is the density of the residual slurry (kg / m 3).

[0011] Furthermore, in the step (2), the concentration of the sodium gluconate solution is 10%; based on the total mass of the residual slurry component as 100%, the amount of sodium gluconate solution added is 0.3‰ to 0.8‰, and the amount of the defoaming agent added is 0.3% to 0.8%.

[0012] Furthermore, the defoamer is any one or more of an organosilicon defoamer, a polyether defoamer, and a silicon polyether defoamer.

[0013] Furthermore, in the step (3), the mass ratio of silica fume, fly ash and water is 3:2:5; based on the total mass of the suspension components as 100%, the amount of super absorbent resin added is 0.2% to 0.5%, and the amount of sodium hexametaphosphate added is 0.4% to 0.6%.

[0014] Furthermore, in step (3), the stirring operation is to place the mixed liquid in a storage tank with a stirring device, and set a stirring program to stir for 5 minutes every 30 minutes.

[0015] Furthermore, in the step (4), the mass ratio of the residual slurry component to the suspension component is 5:2, and the stirring time is 100-150s.

[0016] In a second aspect, the present invention provides a composite admixture of residual slurry of electric poles prepared by the above method.

[0017] In a third aspect, the present invention further provides a high-strength self-leveling concrete mortar for electric poles, which is formed by mixing the above-mentioned electric pole residual slurry composite admixture with concrete.

[0018] Furthermore, the mixing ratio of the pole slurry composite admixture and concrete is specified in the concrete mix ratio; the design method of the concrete mix ratio is: on the basis of the original mix ratio, cement, mixing water and water reducer are reduced; the calculation method of the reduction amount is: the reduction amount of the corresponding component = the amount of the pole slurry composite admixture × the empirical coefficient of the corresponding component; the empirical coefficient is: cement coefficient 0.45, water coefficient 0.38, water reducer coefficient 0.008, according to the reduction calculation results, the amount of each component of the original mix ratio concrete is adjusted.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) The present invention recycles all the residual slurry produced by the centrifugal operation of the electric poles in production, greatly reducing the consumption of cement and tap water. While reducing pollutant emissions, it also reduces production costs, reduces the consumption of cement, a high-energy-consuming product, and reduces carbon emissions.

[0021] (2) The composite admixture of the present invention is pre-mixed and sodium hexametasulfate is added as a dispersant to make the fly ash and silica fume particles evenly dispersed, thereby avoiding the occurrence of agglomeration. At the same time, the contact area between the composite admixture particles and the cement hydration products is increased, which is beneficial to the activity of the composite admixture. When preparing high-strength self-leveling concrete (above C80), it can significantly reduce the water demand of concrete and improve the strength of concrete.

[0022] (3) Concrete will gradually lose moisture during the curing process. The highly absorbent resin component in the composite admixture of the present invention releases moisture under the action of humidity difference to compensate for the loss of moisture. Under the condition of high adhesive dosage, the cement clinker reaction is more complete, which is beneficial to the secondary reaction of the composite admixture, reduces the self-shrinkage and drying shrinkage of the concrete, increases the density and strength of the concrete, and thus improves the durability and impermeability of the concrete.

[0023] (4) The present invention eliminates the problem of emission of inhalable particulate matter during the storage and transportation of powdered raw materials, and greatly reduces the emission of air pollutants in the factory area and factory boundaries. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0025] A composite admixture of residual slurry of electric poles and a preparation method of the composite admixture of residual slurry of electric poles, comprising the following steps:

[0026] (1) Residual slurry homogenization treatment: The density of the collected residual slurry from the poles is tested. The test time is required to be completed within 5 minutes after the poles are centrifuged and the residual slurry is poured out. The amount of saturated calcium hydroxide solution to be added is calculated based on the density of the residual slurry from the poles.

[0027] The amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M;

[0028] Where M is the weight of the residual slurry to be treated, ρ0 is the density of the residual slurry (kg / m 3 ); adding the calculated saturated calcium hydroxide solution into the residual slurry of the electric pole and stirring it thoroughly;

[0029] (2) Based on the total mass of the residual slurry component as 100%, add a sodium gluconate solution (concentration 10%) and stir thoroughly, the addition amount is 0.3‰ to 0.8‰, add 0.3% to 0.8% of a defoaming agent, mix evenly, and obtain a residual slurry component, and place the prepared residual slurry component in a storage tank for standby use;

[0030] The defoamer is any one or more of an organosilicon defoamer, a polyether defoamer, and a silicon polyether defoamer.

[0031] Sodium gluconate solution is used as a retarder for cement-based materials. It has a stable source, stable composition, good retarding effect and is widely used.

[0032] By adding defoaming agent, the air content of concrete can be significantly reduced when it is used for mixing concrete; and the viscosity of the residual slurry can be further reduced after dilution, thereby reducing the surface tension of the bubbles and helping to eliminate the bubbles.

[0033] The setting time of the residual slurry of the pole can be controlled by adjusting the mixing ratio and mixing method of the retarder. The maximum dosage of the retarder shall not exceed 0.8‰. It is produced according to the residual slurry recycling process. Under normal circumstances, it is not necessary to add a retarder. In special circumstances, the residual slurry is left to stand for too long, and a retarder is added. The residual slurry produced after the residual slurry mixed with the retarder is used to produce the pole shall not be further added with the retarder to avoid the impact of excessive retarder on the demoulding strength. The retarder should be added within 5 minutes after the residual slurry is poured out after the centrifugation of the pole is completed. If the time is too long, the residual slurry will start to enter the heating and condensation stage, which will affect its storage time and use effect. The dosage of the retarder is 0.3‰~0.8‰. If the dosage is too low, the fluidity loss will be large, and if the dosage is too high, the demoulding strength of the concrete will be affected.

[0034] (3) Silica fume, fly ash and water are mixed in a mass ratio of 3:2:5, and based on 100% of the suspension component, 0.2% to 0.5% of a highly absorbent resin is added as an internal curing agent and 0.4% to 0.6% of sodium hexametaphosphate is added as a dispersant, and the mixture is placed in a storage tank with a stirring device, stirred evenly, and a stirring program is set to stir for 5 minutes every 30 minutes. After mixing evenly, the suspension is ensured to be uniform, and a suspension component that can be stored for a long time is obtained;

[0035] Sodium hexametaphosphate is added as a dispersant to ensure the uniformity of the suspension; super absorbent resin is a new type of functional polymer material with extremely strong water absorption capacity and excellent water retention performance. This material can absorb hundreds or thousands of times its own weight of water to form a gel-like substance, which can keep the water from separating even under pressure. Super absorbent polymer [3 (SAP) is a kind of strong hydrophilic group containing carboxyl (-COOH) and hydroxyl (-OH). They can form hydrogen bonds with water to form hydration and quickly absorb liquid water dozens or even thousands of times their own weight to form a gel. Super absorbent resin has a three-dimensional cross-linked network structure and can fix free water inside the polymer network through swelling. Therefore, it has good water retention even under pressure, but it is a lightly cross-linked polymer that can slowly release water in dry air. Unlike general absorbent materials, it has extremely strong water retention capacity. Even under high pressure conditions, the absorbed water is difficult to overflow naturally, but the swollen super absorbent polymer will release water when the environmental pH value or ion concentration is high. In the cement hydration process, after the cement minerals begin to hydrate, the cations (mainly Ca2+) generated by the hydration dissolve into the water, and the pH value of the system rises. The increase in the cation concentration prompts the SAP to continuously release water and supply the water required for further hydration of the cement. In addition, since the SAP and the unreleased water inside it are combined in the form of hydrogen bonds, the water is fixed on the polymer chain and hidden in the network structure of the polymer. Therefore, the evaporation of this part of water requires a lot of energy. In addition, the film formation on the surface of the SAP particles slows down the drying speed, thereby slowing down the water loss caused by evaporation.

[0036] (4) Weigh the slurry component and the suspension component in a mass ratio of 5:2, mix and stir for 100-150 seconds, and obtain the pole slurry composite admixture after mixing evenly.

[0037] Composite admixtures contain a large amount of active oxides, such as silica, Al2O3, Fe2O3, etc. These substances react with alkaline substances in water and cement hydration products to form some new compounds, such as calcium silicate, calcium aluminate, calcium ferrite, etc. These new compounds can fill the pores and voids in concrete, increase the density and strength of concrete, and thus improve the durability and impermeability of concrete.

[0038] A high-strength self-leveling concrete mortar for electric poles is prepared by mixing the above-mentioned electric pole residual slurry composite admixture with concrete. During production, the above-mentioned electric pole residual slurry composite admixture is added into a mixing tank and mixed with concrete, and the mixing ratio is specified in the concrete mix ratio.

[0039] The design method of concrete mix ratio is: determine the empirical coefficient, and obtain the best mix ratio of concrete according to the cement coefficient of 0.45, the water coefficient of 0.38, and the water reducer coefficient of 0.008; when using the composite admixture of pole slurry, on the basis of the original mix ratio of mixing water: 175kg, cement: 460kg, sand: 780kg, gravel: 1020kg, and water reducer 7.2kg, reduce the cement, mixing water, and water reducer, and the reduction amount of the corresponding component = the amount of composite admixture of pole slurry × the empirical coefficient of the corresponding component.

[0040] By using pre-mixed pole slurry composite admixtures, the occurrence of agglomeration is avoided. When preparing high-strength self-leveling concrete, the admixture can be evenly dispersed, and the cement in the slurry is also in a uniformly dispersed state, avoiding cement and admixture agglomeration to wrap water, allowing water to fully play its positive role in fluidity, making it easier for the water reducer to combine with the powder particles and play a greater role, which can significantly reduce the water demand of concrete and improve the strength of concrete.

[0041] (I) Preparation of a composite admixture of residual slurry of electric poles

[0042] Synthesis example 1

[0043] A method for preparing a composite admixture of residual slurry of electric poles comprises the following steps:

[0044] (1) Homogenization of residual slurry: The density of the collected 20 kg residual slurry from the poles was tested within 5 minutes after the residual slurry was poured out after the poles were centrifuged. The density of the residual slurry from the poles was 1.85 kg / m 3 ; Calculate the amount of saturated calcium hydroxide solution to be added based on the residual slurry density of the pole;

[0045] The amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M;

[0046] Add the calculated 19.25 kg saturated calcium hydroxide solution into the residual slurry of the electric pole and stir thoroughly;

[0047] (2) Based on the total mass of the residual slurry component as 100%, 0.3‰ sodium gluconate solution (concentration 10%) is added and stirred thoroughly, and then 0.3% of an organosilicon defoamer is added and mixed evenly to obtain a residual slurry component, and the prepared residual slurry component is placed in a storage tank for standby use;

[0048] (3) Silica fume, fly ash and water are mixed in a mass ratio of 3:2:5, and 0.2% of super absorbent resin and 0.4% of sodium hexametaphosphate are added to the total mass of the suspension component as 100%, and the mixture is placed in a storage tank with a stirring device, stirred evenly, and a stirring program is set to stir for 5 minutes every 30 minutes. After mixing evenly, the suspension is ensured to be uniform, and a suspension component that can be stored for a long time is obtained;

[0049] (4) The slurry component and the suspension component were weighed in a mass ratio of 5:2, mixed and stirred for 100 seconds, and after mixing evenly, a composite admixture of the pole slurry was obtained.

[0050] Synthesis example 2

[0051] A composite admixture of residual slurry of electric poles is composed of the following components: residual slurry of electric poles, saturated calcium hydroxide solution, sodium gluconate solution, polyether defoamer, silica ash, fly ash, sodium hexametaphosphate, highly absorbent resin and water.

[0052] The preparation method of the composite admixture of residual slurry of electric poles comprises the following steps:

[0053] (1) Homogenization of residual slurry: The density of the collected 20 kg residual slurry from the poles was tested within 5 minutes after the residual slurry was poured out after the poles were centrifuged. The density of the residual slurry from the poles was 1.85 kg / m 3 ; Calculate the amount of saturated calcium hydroxide solution to be added based on the residual slurry density of the pole;

[0054] The amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M;

[0055] Add the calculated 19.25 kg saturated calcium hydroxide solution into the residual slurry of the electric pole and stir thoroughly;

[0056] (2) Based on the total mass of the residual slurry component as 100%, 0.55‰ sodium gluconate solution (concentration 10%) is added and stirred thoroughly, and then 0.55% polyether defoamer is added and stirred evenly to obtain the residual slurry component, and the prepared residual slurry component is placed in a storage tank for standby use;

[0057] (3) Silica fume, fly ash and water are mixed in a mass ratio of 3:2:5, and 0.35% of super absorbent resin and 0.5% of sodium hexametaphosphate are added based on the total mass of the suspension component as 100%, and the mixture is placed in a storage tank with a stirring device, stirred evenly, and a stirring program is set to stir for 5 minutes every 30 minutes. After mixing evenly, the suspension is ensured to be uniform, and a suspension component that can be stored for a long time is obtained;

[0058] (4) The slurry component and the suspension component were weighed in a mass ratio of 5:2, mixed and stirred for 120 seconds, and after mixing evenly, a composite admixture of the pole slurry was obtained.

[0059] Synthesis example 3

[0060] A composite admixture of residual slurry of electric poles is composed of the following components: residual slurry of electric poles, saturated calcium hydroxide solution, sodium gluconate solution, polyether defoamer, silica ash, fly ash, sodium hexametaphosphate, highly absorbent resin and water.

[0061] The preparation method of the composite admixture of residual slurry of electric poles comprises the following steps:

[0062] (1) Homogenization of residual slurry: The density of the collected 20 kg residual slurry from the poles was tested within 5 minutes after the residual slurry was poured out after the poles were centrifuged. The density of the residual slurry from the poles was 1.85 kg / m 3 ; Calculate the amount of saturated calcium hydroxide solution to be added based on the residual slurry density of the pole;

[0063] The amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M;

[0064] Add the calculated 19.25 kg saturated calcium hydroxide solution into the residual slurry of the electric pole and stir thoroughly;

[0065] (2) Based on the total mass of the residual slurry component as 100%, 0.8‰ sodium gluconate solution (concentration 10%) is added and stirred thoroughly, and then 0.8% polyether defoamer is added and mixed evenly to obtain the residual slurry component, and the prepared residual slurry component is placed in a storage tank for standby use;

[0066] (3) Silica fume, fly ash and water are mixed in a mass ratio of 3:2:5, and 0.5% of super absorbent resin and 0.6% of sodium hexametaphosphate are added based on the total mass of the suspension component as 100%, and the mixture is placed in a storage tank with a stirring device, stirred evenly, and a stirring program is set to stir for 5 minutes every 30 minutes. After mixing evenly, the suspension is ensured to be uniform, and a suspension component that can be stored for a long time is obtained;

[0067] (4) The slurry component and the suspension component were weighed in a mass ratio of 5:2, mixed and stirred for 150 seconds, and after mixing evenly, a composite admixture of the pole slurry was obtained.

[0068] (II) Preparation of high-strength self-leveling concrete mortar for electric poles

[0069] Example 1

[0070] A high-strength self-leveling concrete mortar for electric poles is prepared by mixing the electric pole residual slurry composite admixture of Synthesis Example 1 with concrete. During production, the electric pole residual slurry composite admixture of Synthesis Example 1 is added to a mixing tank and mixed with concrete, and the mixing ratio is specified in the concrete mix ratio.

[0071] The design method of concrete mix ratio is: according to the cement coefficient of 0.45, the water coefficient of 0.38 and the water reducing agent coefficient of 0.008, the amount of each component in the concrete is adjusted. These coefficients are used to adjust the amount of each component in the concrete; when the pole residual slurry composite admixture is used, the cement, mixing water and water reducing agent are reduced on the basis of the original mix ratio of mixing water: 175kg, cement: 460kg, sand: 780kg, gravel: 1020kg, and water reducing agent 7.2kg. The reduction amount of the corresponding components is:

[0072] The reduction of mixing water = the amount of composite admixture of pole residual slurry × 0.38,

[0073] Cement reduction = amount of composite admixture of pole slurry × 0.45,

[0074] The reduction amount of water reducing agent = the amount of composite admixture of residual slurry of electric pole × 0.008,

[0075] Adjust the original mix ratio based on the reduction calculation results.

[0076] Example 2

[0077] A high-strength self-leveling concrete mortar for electric poles is prepared by mixing the electric pole residual slurry composite admixture of Synthesis Example 2 with concrete. During production, the electric pole residual slurry composite admixture of Synthesis Example 2 is added to a mixing tank and mixed with concrete, and the mixing ratio is specified in the concrete mix ratio.

[0078] The design method of concrete mix ratio is: according to the cement coefficient of 0.45, the water coefficient of 0.38 and the water reducing agent coefficient of 0.008, the amount of each component in the concrete is adjusted; when the composite admixture of the residual slurry of the electric pole is used, the cement, mixing water and water reducing agent are reduced on the basis of the original mix ratio of mixing water: 175kg, cement: 460kg, sand: 780kg, gravel: 1020kg, and water reducing agent 7.2kg. The reduction amount of the corresponding components is:

[0079] The reduction of mixing water = the amount of composite admixture of pole residual slurry × 0.38,

[0080] Cement reduction = amount of composite admixture of pole slurry × 0.45,

[0081] The reduction amount of water reducing agent = the amount of composite admixture of residual slurry of electric pole × 0.008,

[0082] Adjust the original mix ratio based on the reduction calculation results.

[0083] Example 3

[0084] A high-strength self-leveling concrete mortar for electric poles is prepared by mixing the electric pole residual slurry composite admixture of Synthesis Example 3 with concrete. During production, the electric pole residual slurry composite admixture of Synthesis Example 3 is added to a mixing tank and mixed with concrete, and the mixing ratio is specified in the concrete mix ratio.

[0085] The design method of concrete mix ratio is: according to the cement coefficient of 0.45, the water coefficient of 0.38 and the water reducing agent coefficient of 0.008, the amount of each component in the concrete is adjusted; when the composite admixture of the residual slurry of the electric pole is used, the cement, mixing water and water reducing agent are reduced on the basis of the original mix ratio of mixing water: 175kg, cement: 460kg, sand: 780kg, gravel: 1020kg, and water reducing agent 7.2kg. The reduction amount of the corresponding components is:

[0086] The reduction of mixing water = the amount of composite admixture of pole residual slurry × 0.38,

[0087] Cement reduction = amount of composite admixture of pole slurry × 0.45,

[0088] The reduction amount of water reducing agent = the amount of composite admixture of residual slurry of electric pole × 0.008,

[0089] Adjust the original mix ratio based on the reduction calculation results.

[0090] Comparative Example 1

[0091] In this comparative example, a composite admixture of pole residual slurry with a density detection time of 5.5 minutes is mixed with concrete to prepare high-strength self-leveling concrete mortar for poles. The remaining raw materials and preparation method of the composite admixture of pole residual slurry are consistent with those in Synthesis Example 1, and the steps and parameters of the high-strength self-leveling concrete mortar for poles are consistent with those in Example 1.

[0092] Comparative Example 2

[0093] In this comparative example, a composite admixture of pole slurry with a sodium gluconate solution added in an amount of 0.2‰ is mixed with concrete to prepare high-strength self-leveling concrete mortar for poles. The remaining raw materials and preparation methods of the composite admixture of pole slurry are consistent with those in Synthesis Example 1, and the steps and parameters of the high-strength self-leveling concrete mortar for poles are consistent with those in Example 1.

[0094] Comparative Example 3

[0095] In this comparative example, a composite admixture of pole slurry with a sodium gluconate solution added in an amount of 0.9‰ is mixed with concrete to prepare high-strength self-leveling concrete mortar for poles. The remaining raw materials and preparation method of the composite admixture of pole slurry are consistent with those in Synthesis Example 1, and the steps and parameters of the high-strength self-leveling concrete mortar for poles are consistent with those in Example 1.

[0096] Comparative Example 4

[0097] In this comparative example, a composite admixture of pole residual slurry in which an excessive amount of saturated calcium hydroxide solution is added during the residual slurry homogenization treatment is mixed with concrete to prepare high-strength self-leveling concrete mortar for poles. The remaining steps and parameters of the composite admixture of pole residual slurry are consistent with those in synthesis example 1, and the raw materials of the high-strength self-leveling concrete mortar for poles are consistent with those in Example 1.

[0098] Comparative Example 5

[0099] In this comparative example, a composite admixture of pole residual slurry in which the amount of saturated calcium hydroxide solution added during the residual slurry homogenization treatment is mixed with concrete to prepare high-strength self-leveling concrete mortar for poles. The remaining steps and parameters of the composite admixture of pole residual slurry are consistent with those in Synthesis Example 1, and the raw materials of the high-strength self-leveling concrete mortar for poles are consistent with those in Example 1.

[0100] Comparative Example 6

[0101] This comparative example does not involve the use of the pole residual slurry composite admixture of the present invention, and the concrete mortar is directly prepared from the original concrete mix ratio (mixing water: 175kg, cement: 460kg, sand: 780kg, gravel: 1020kg, and water reducer 7.2kg).

[0102] Comparative Example 7

[0103] The difference between this comparative example and the embodiment is that the cement coefficient in the design method of the concrete mix ratio is 0.55, and the remaining steps and parameters are consistent with those in embodiment 1.

[0104] Comparative Example 8

[0105] The difference between this comparative example and the embodiment is that the water coefficient in the design method of the concrete mix ratio is 0.48, and the remaining steps and parameters are consistent with those in embodiment 1.

[0106] Comparative Example 9

[0107] The difference between this comparative example and the embodiment is that the water coefficient in the design method of the concrete mix ratio is 0.25, and the remaining steps and parameters are consistent with those in embodiment 1.

[0108] Comparative Example 10

[0109] Compared with the embodiment, the difference between this comparative example and the embodiment is that the water reducing agent coefficient in the design method of the concrete mix ratio is 0.009, and the remaining steps and parameters are consistent with those in embodiment 1.

[0110] Comparative Example 11

[0111] The difference between this comparative example and the embodiment is that the water reducing agent coefficient in the design method of the concrete mix ratio is 0.007, and the remaining steps and parameters are consistent with those in Example 1.

[0112] Application Examples

[0113] According to the above concrete mix design method, high-strength self-leveling concrete mortar for electric poles of Examples 1-3 and Comparative Examples 1-11 were prepared; the concrete mix ratios are shown in Table 1:

[0114] Table 1 Concrete mix ratio (kg / m 3 )

[0115]

[0116] The high-strength self-leveling concrete mortar for electric poles prepared in Examples 1-3 and Comparative Examples 1-11 was tested for various performance indicators. The test method was carried out in accordance with the relevant requirements of "GB / T 50107-2010 Concrete Strength Test and Evaluation Standard" and "GB / T50080-2016 Ordinary Concrete Mixture Performance Test Method Standard". The results are shown in Table 2.

[0117] Table 2 Related performance test results

[0118]

[0119]

[0120] Performance test data conclusion analysis:

[0121] First, by comparing Example 1 with Comparative Examples 1-3, in Comparative Example 1, the density detection time of the residual slurry of the electric pole is too long, resulting in the residual slurry being left standing for too long, and the residual slurry has begun to enter the heating and coagulation stage. When the retarder is subsequently added, it will affect the retarding effect, thereby affecting the expansion of the concrete; in Comparative Example 2, the amount of the retarder sodium gluconate solution added is too low, resulting in a large loss of fluidity; and in Comparative Example 3, the amount of the retarder sodium gluconate solution added is too high, resulting in prolonged concrete coagulation time, thereby affecting the demolding strength; this shows that the present application adjusts the mixing ratio (0.3‰~0.8‰) and mixing method (adding within 5 minutes after the residual slurry is poured out) of the retarder (sodium gluconate solution), which has the effect of maintaining the fluidity of the concrete without affecting the demolding strength.

[0122] Secondly, comparing Example 1 with Comparative Examples 4-6, in Comparative Example 4, too much saturated calcium hydroxide solution was added during the homogenization treatment of the residual slurry, which had the effect of reducing the demolding strength; while in Comparative Example 5, the amount of saturated calcium hydroxide solution added was too low, which had the effect of poor fluidity; Comparative Example 6 does not involve the use of the pole composite admixture of the present invention, and is a pole concrete mortar directly prepared by adopting the original concrete mix ratio, and its fluidity performance is poor.

[0123] Again, by comparing Examples 1-3 and Comparative Examples 7-11, the best mix ratio of the concrete of the present invention is determined; in Comparative Example 7, the mix ratio of the concrete is calculated according to the cement coefficient of 0.55, and the reduction amount of cement becomes higher, resulting in a decrease in demolding strength; in Comparative Example 8, the mix ratio of the concrete is calculated according to the water coefficient of 0.48, and the reduction amount of water becomes higher, resulting in a decrease in demolding strength; in Comparative Example 9, the mix ratio of the concrete is calculated according to the water coefficient of 0.25, and the reduction amount of water becomes lower, resulting in an increase in demolding strength; in Comparative Example 10, the mix ratio of the concrete is calculated according to the water reducer coefficient of 0.009, and the reduction amount of the water reducer becomes higher, resulting in a decrease in fluidity; in Comparative Example 11, the mix ratio of the concrete is calculated according to the water reducer coefficient of 0.007, and the reduction amount of the water reducer becomes lower, resulting in an increase in fluidity; This shows that the concrete mix ratio determined by the cement coefficient / water coefficient / water reducer of 0.45 / 0.38 / 0.008 in the concrete mix ratio design method of the present application has better compressive strength and working performance of the prepared concrete mortar.

[0124] The following conclusions can be drawn from the above embodiments:

[0125] The concrete mortar prepared by using the composite admixture of residual slurry from electric poles and the concrete mix design method of the present application has been verified through strength tests and can achieve an expansion of more than 650mm, high compressive strength, and a strength of more than 65MPa at the 28th day, good fluidity, and a product without cracks, which is much higher than the performance of general concrete; therefore, the production of concrete mortar using the composite admixture of residual slurry from electric poles prepared by the method of this embodiment can improve the density of the concrete itself, reduce cracks and harmful holes, and improve the working performance of the concrete.

[0126] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A method for preparing a composite admixture of residual slurry of electric poles, characterized in that: The following steps are involved: (1) Residual slurry homogenization treatment: The collected pole residual slurry is subjected to density detection, and the amount of saturated calcium hydroxide solution to be added is calculated according to the density. The calculated saturated calcium hydroxide solution is added to the pole residual slurry and stirred thoroughly; (2) adding sodium gluconate solution and defoamer, and mixing evenly to obtain a residual slurry component; (3) mixing silica fume, fly ash and water, adding super absorbent resin and sodium hexametaphosphate and stirring, and mixing evenly to obtain a suspension component; (4) The residual slurry component and the suspension component are mixed and stirred evenly to obtain the electric pole residual slurry composite admixture.

2. The preparation method according to claim 1, characterized in that: In the step (1), the time for detecting the density of the residual slurry on the electric pole is within 5 minutes after the residual slurry on the electric pole is poured out; The amount of saturated calcium hydroxide solution added is: M w =(2.75ρ0×10 -3 -4.125)×M; where M is the weight of the residual slurry to be treated, and ρ0 is the density of the residual slurry (kg / m 3 ).

3. The preparation method according to claim 1, characterized in that: In the step (2), the concentration of the sodium gluconate solution is 10%; based on the total mass of the residual slurry component as 100%, the amount of the sodium gluconate solution added is 0.3‰ to 0.8‰, and the amount of the defoaming agent added is 0.3% to 0.8%.

4. The preparation method according to claim 3, characterized in that: The defoamer is any one or more of an organosilicon defoamer, a polyether defoamer, and a silicon polyether defoamer.

5. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of silica fume, fly ash and water is 3:2:5; based on the total mass of the suspension components as 100%, the amount of super absorbent resin added is 0.2% to 0.5%, and the amount of sodium hexametaphosphate added is 0.4% to 0.6%.

6. The preparation method according to claim 1, characterized in that: In the step (3), the stirring operation is to place the mixed liquid in a storage tank equipped with a stirring device and set a stirring program to stir for 5 minutes every 30 minutes.

7. The preparation method according to claim 1, characterized in that: In the step (4), the mixing ratio of the residual slurry component to the suspension component is 5:2 by mass, and the stirring time is 100-150s.

8. A composite admixture of residual slurry of electric poles, characterized in that: The invention is prepared by the preparation method of the composite admixture of residual slurry of electric poles as claimed in any one of claims 1 to 7.

9. A high-strength self-leveling concrete mortar for electric poles, characterized in that: The composite admixture of the residual slurry of the electric pole as claimed in claim 8 is mixed with concrete.

10. The high-strength self-leveling concrete mortar for electric poles according to claim 9, characterized in that: The mixing ratio of the composite admixture of the residual slurry of the electric pole and the concrete is specified in the concrete mix ratio; The design method of the concrete mix ratio is: based on the original mix ratio, cement, mixing water and water reducing agent are reduced, and the reduction amount is calculated as follows: the reduction amount of the corresponding component = the amount of the composite admixture of the residual slurry of the electric pole × the empirical coefficient of the corresponding component; The empirical coefficients are: cement coefficient 0.45, water coefficient 0.38, water reducing agent coefficient 0.008; According to the reduction calculation results, the dosage of each component of the original mix concrete is adjusted.